Imagining A New World: Soekarno’s Speeches 1958-1965 - Wijanarko, Nugroho Bayu (Universitas Negeri Semarang, 2025)
This research focuses on how the views and ideas of the Indonesian people faced the global situation during the Cold War, which were represented in President Sukarno's speeches during the period 1958-1965. The method used in this research is the historical method with the main primary source in the form of 29 presidential speech manuscripts obtained from the Indonesian National Archives (ANRI) and supported by a number of literature which is then continued in source criticism and interpretation, to produce historiography. The findings of this research are that the new world envisioned by President Sukarno and conveyed in his speeches, is a world that begins with independence and is full of friendship, based on the spirit of solidarity and socialism.